Online learning for innovation method to improve students' characteristic - Safruddin, Muchamad; Priyanto, Sigit; Amin, Muhammad Khoirul (Universitas Muhammadiyah Magelang, 2023)
The development of the education system has changed due to the impact of the COVID-19 virus. Online learning has become an accessible method during the pandemic. However, this method influences the students' characteristics. Also, investigating related to these characteristics changes has not been explored in the literature. Therefore, the study aimed to evaluate the impact of online learning on students' characteristics. The study used a descriptive study involving 62 respondents. Inclusion and exclusion were determined. The instruments were questionnaires. Spearman's rank correlation coefficient was also used for data analysis. Our study showed that online learning does not build the character of elementary school children (p>0.05). Further studies are needed to evaluate these variables in another population. Keywords: Online learning; community nursing; education system; students’ characteristics; nursing care